Measuring up: testing measurement equivalence and developing a concise organizational transparency scale - Stuckey, Leah Shely Klos (My University, 2025)
The current study had two aims, the first was to test the measurement equivalence (ME) of an organizational transparency scale, and the second aim was to develop a shorter organizational transparency scale. For the first aim, multi-group confirmatory factor analysis and item response theory (IRT) methods were used to investigate two research questions regarding the potential ME of the organizational transparency scale between public and private sector employees as well as employees who belong to one of two different government agencies in the same facility within the public sector. The results found evidence in support of ME in both cases of the private vs. public sector comparison and between the two agencies within the private sector, although the latter did have differential item functioning for one item. The ME results provide evidence for the benefits of utilizing both factor and item level analyses to capture a fuller picture and provide more nuanced information. For the second aim, IRT was used to develop a more concise organizational transparency scale. The developed shortened scale was made up of eight items and demonstrated validity and reliability. The newly shortened scale will hopefully aide in spurring more research on organizational transparency and in turn further develop its nomological network as researchers and practitioners alike will now be able to incorporate it more easily into their surveys with the reduction in survey length compared to the original 23-item scale and they can balance it with considerations of compensation costs, total survey length in conjunction with other constructs, participant experience, etc. With these two lines of research, the study findings have the potential to stimulate more research on the construct of organizational transparency with knowledge on the generalizability of the scale across industry sectors and within the public sector as well as through the creation of the shortened scale which provides benefits to survey participants, researchers, and practitioners.
Keywords: Organizational transparency; Measurement equivalence; Scale development